Study of fixed point theorem in complex valued intuitionistic fuzzy metric space - Ram Milan Singh (Journal of Hyperstructures)
We will show several common fixed point theorems for contraction condition satisfying certain requirements in complex valued intuitionistic fuzzy metric spaces in this study.